Effect of fibular repositioning taping in adult basketball players with chronic ankle instability: a randomized, placebo-controlled, crossover trial - Alves, Y.; Ribeiro, F.; Silva, A. G. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Chronic ankle instability presents a high incidence and prevalence in basketbal players. It is important to develop strategies to reduce the functional and mechanical limitations resulting from this condition. The aim of this study was to compare the effect of Mulligan`s fibular repositioning taping with a placebo taping immediatly after application and after a running test (Yo-Yo intermittent recovery test). METHODS: Sixteen adult basketball players (10 male, 6 female) with chronic ankle instability and mean age 21.50±2.76 years old. Assessment of static postural control (15 seconds of unipedal stance test with eyes closed in a force platform), functional performance (figure-of-8 hop test and lateral hop test) and neuromuscular control (peroneus longus latency time in sudden inversion) in two conditions: Mulligan and placebo. RESULTS: No significant effect was found for the intervention factor in both hop tests (P>0.170), but there was a significant effect for the time factor (P<0.03). For the peroneus longus latency time, there was a significant interaction between factors (P=0.028) and also for time (P=0.042). No significant effect was found for any of the static postural control variables (area, speed and total displacement) (P=0.10). CONCLUSIONS: There was no differences between Mulligan`s fibular repositioning taping and Placebo taping in postural control and functional performance in basketball players with chronic ankle instability. However, Mulligan`s taping appears to reduce peroneus longus latency time after a running when compared with a placebo taping.